Biodiversity of hydrolytic enzymes-producing soil bacteria from a Durian Park, Jombang, Indonesia: Beneficial prospect for sustainable agriculture - NI’MATUZAHROH NI’MATUZAHROH; MOCH. AFFANDI; AGUS SUPRIYANTO; BERLIAN RUSTANTINA; LAILY AINUN JAIYAH; AISYAH RAHMAWATI; HESTI NURHAYATI; SILVIA KURNIA SARI; ANA MARIATUL KHIFTIYAH; DAMAN HURI (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Ni’matuzahroh, Affandi M, Supriyanto A, Rustantina B, Jaiyah LA, Rahmawati A, Nurhayati H, Sari SK, Khiftiyah AM, Huri D. 2024. Biodiversity of hydrolytic enzymes-producing soil bacteria from a Durian Park, Jombang, Indonesia: Beneficial prospect for sustainable agriculture. Biodiversitas 25: 392-403. Biofertilizer is an alternative to chemical fertilizer that can enhance plant growth but is specific to certain plants and soils. Various biofertilizers have been produced, but the specific biofertilizers to enhance durian growth have not been widely available. This study aims to determine the potential of hydrolytic enzyme-producing bacteria, one of the microbial components of biofertilizers, in the De Durian Park (DDP) area, Wonosalam, Jombang District, Indonesia. The bacteria were isolated using the selective medium plating technique. The obtained isolates were screened for their ability to produce cellulase, amylase, protease, and lipase. The clear zone around the colony indicated the ability of the isolates to produce hydrolytic enzymes, and then the clear zone index was obtained. The best three isolates for each enzyme production were characterized macroscopically, microscopically, and biochemically, then identified using 16S rRNA gene sequence analysis. Fifty-two isolates were successfully obtained from the soil of DDP. The best three cellulolytic bacteria had indices ranging from 1.83 to 2.14, categorized as moderate-strong, identified as Bacillus anthracis, B. pacificus, and B. cereus. The amylolytic bacteria ranged from 1.25 to 1.35, categorized as moderate, and identified as Bacillus anthracis, B. paranthracis, and B. paramycoides. The proteolytic bacteria ranged from 1.33 to 1.50, categorized as moderate, identified as B. pumilus, B. paramycoides, and B. cereus. The lipolytic bacteria ranged from 1.94 to 3.87, categorized as moderate-strong, and were identified as Enterobacter sichuanensis, B. pacificus, and E. asburiae. These cellulolytic, amylolytic, proteolytic, and lipolytic bacteria have the potency as candidates for a biofertilizer formula.